FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN - Jennifer Antonius, Tony Sudirgo (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to obtain empirical evidence regarding the effect of capital structure, firm age, firm size, growth opportunities, and earning per share on company performance at consumption company listed in Indonesia Stock Exchange during 2015-2017. The sampling method used in this study to collect research sample is purposive sampling method, with the result that 35 company at consumption company listed in Indonesia Stock Exchange during 2015-2017 collected as the research sample. Data used for this study is obtained from audited financial statement for the year ended December 31th during 2015- 2017. Panel data regression is used to test the hypothesis using Eviews 10.0. The result of this study shows that capital structure, growth opportunities, and earning per share have significantly effect on company performance, while firm age and firm size do not have significant effect on company performance.